Need Of Collaboration Of Ayurveda With Other Systems Of Health Science: A Review - Sharma, Deepak; Bhatnagar, Vikash; Lahange, Sandeep M; Sharma, Gaurav; Kumawat, Neha (International Research Journal of Ayurveda & Yoga, 2021)
Modern period is era of technology and full of information. Everyone is connected to each other in one way or other. Science, technology, infrastructure, etc. are developing together. The modern scientific medicine has begun to recognize that the traditional Indian system of medicine, Ayurveda, is an extensive storehouse of knowledge relevant to human health, disease, medicines and general health-care. In present era there is intense need of collaboration but without excluding the basic subject and concepts of Ayurveda. We can easily use the vast potential of Ayurveda available along with the other sciences in maintaining and improving the existing health structure and hygienic status of public.